BELAJAR KOLABORASI BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KEMAMPUAN SPEAKING SISWA SELAMA PANDEMIK COVID 19 - Ramli Ramli; Faisal Adi Putra; Andi Hamzah Fansury (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aims to investigate the integration of technology for students to learn collaboratively in practicing their speaking. This study took another possible way to use the google meet link through Google classroom to meet students and improve their speaking on different topics. This research applied a pre-experimental study. In semester six, the population was all students, English department Universitas Borneo Tarakan. Through random sampling, the samples were Class A consisting of 31 students. The instrument was a spoken test administered as a pre-test and post-test and speaking scoring rubric and the data on students’ speaking was analyzed using SPSS 17. The result showed the value of t-count greater than t-table (26 372> 2042), and a p-value less than α (0.000 <0.050) which means that there are significant differences between pre-and post-by-paired t speaking measured scoring. As a result, technology-based online collaborative learning can significantly increase the total score of students' speaking skills in English. This research was expected to contribute to the body of knowledge on how technology brought a change and opportunity to keep learning during pandemics and this study also tended to assist the students to improve their spoken language